2021
DOI: 10.1186/s12917-021-03038-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical insights into the three-dimensional anatomy of cheek teeth in alpacas based on micro-computed tomography. Part 1: mandibular cheek teeth

Abstract: Background Despite dental disease being a common health concern in alpacas, important dental pathology including apical infection, remains poorly understood. Treatment options are limited compared to veterinary dentistry techniques in other species. The primary goal of this study was to increase understanding of the external and internal anatomy of mandibular cheek teeth to enable the development of tooth sparing techniques in this species. Also, an objective evaluation of the sub-occlusal dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Hence, apical infections, previously termed tooth root abscesses, are the most common dental condition affecting alpacas, primarily involving the cheek teeth ( 1 ). Recently, micro-computed tomographic studies have confirmed that adjacent tooth roots from different cheek teeth can physically contact each other ( 7 , 8 ). However, up until now, no histological studies have been published focusing on the normal histological findings at the level of the cheek teeth in this species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, apical infections, previously termed tooth root abscesses, are the most common dental condition affecting alpacas, primarily involving the cheek teeth ( 1 ). Recently, micro-computed tomographic studies have confirmed that adjacent tooth roots from different cheek teeth can physically contact each other ( 7 , 8 ). However, up until now, no histological studies have been published focusing on the normal histological findings at the level of the cheek teeth in this species.…”
Section: Discussionmentioning
confidence: 99%
“…The microscopical characteristics of the dental hard substances and dental and periodontal tissues were described and alpaca specific structures were identified. Referencing to specific pulp horns and root canals was based on a specific numbering system for alpaca cheek teeth ( 7 , 8 ). A classification of different types of dentin was performed based on the classification system as proposed by Dacre et al ( 11 ) in other hypsodont species.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have also been described in other brachydont species such as dogs ( 22 26 ) and cats ( 27 , 28 ). Additionally, even hypsodont cheek teeth of alpacas ( 29 ) and equine incisors can have accessory canals.…”
Section: Introductionmentioning
confidence: 99%